Results of positive proximal margin after resection for hilar cholangiocarcinoma: An analysis of 42 cases - Volkan Öter; İlter Özer and Tahsin Dalgıç and Cemil Binarbaşı and Murat Ulaş and Erdal Birol Bostancı (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Hilar cholangiocarcinoma (HC) is a tumor that invades the confluence of the left and right hepatic bile ducts. Surgery is the definitive treatment but is also technically demanding. Here, we report our experience on 42 patients who underwent surgical resection for HC. The aim of the present study was to evaluate the margin status of resected specimens on frozen sections and the impact of R1 resection margin on survival. Materials and Methods: A total of 42 patients with HC who underwent surgical resection in our clinic between January 2008 and January 2017 were included in the study. Patients’ charts were evaluated retrospectively. Results: The 1-, 2-, and 4-year overall survival rates of the 42 patients were 76.2%, 40%, and 10.7%, respectively. The median survival rates of the patients with negative and positive proximal surgical margins were 22 (11.93-32.06) and 17 (14.43-19.56) months, respectively. There was no statistically significant difference between these two groups. Conclusion: In HC, surgery achieving negative proximal surgical margin is often very difficult. Our results demonstrate that frozen sections are reliable for the assessment of the invasion status of the proximal and distal ductal surgical margins. Although complete resection is potentially curative, survival of the patients with HC is still poor. If there is no distant metastasis at the time of diagnosis, then extirpating surgery should be encouraged as survival of the patients with positive and negative margins is not significantly different. Cite this article as: Öter V, Özer İ, Dalgıç T, Binarbaşı C, Ulaş M, Bostancı EB. Results of positive proximal margin after resection for hilar cholangiocarcinoma: An analysis of 42 cases. Turk J Gastroenterol 2019; 30: 88-94.